PENGEMBANGAN AUTO CANCEL SEIN BERBASIS MIKROKONTROLER PADA SEPEDA MOTOR - Adhi Satria Laksana; Husin Bugis; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The aims of this research are: (1) to develop of auto cancel sein based on microcontroller for motorcycle; (2) to analyze the performance of system auto cancel sein based on microcontroller on a motorcycle. Development of system auto cancel sein based on microcontroller was done in 3 stages: (1) needs analysis; (2) design system hardware; (3) design system software. the auto cancel sein was applied on Honda Supra X motorcycle Tested with U-Turn test. The results of this study are: (1) the auto cancel sein composed three sensors (speed sensor, steer position sensor, and tilt sensor) used to read the input data of. Microcontroller used for data processing. the actuator (output) used 2 channel relay module; (2) the application on Honda Supra X motorcycle showed that auto cancel sein can work properly and correctly for speed of 10 km/h, 20 km/h, 30 km/h, 40 km/h, 50 km/h.